ARTISTIC FEATURES OF OGAHI’S GHAZAL "EY, QUYOSH YUZING OCHGIN (World Bulletin of Social Sciences, 2021)
This article is dedicated to the analysis of the ghazal "Ey, quyosh yuzing ochgin…" by Muhammad Reza Agahi, a skilled translator, poet and statesman. The article describes the structure of the ghazal, its poetic art, rhyme and spiritual aspects on a scientific basis. Here are some of the ones I found to be interesting: There are also enough conclusions about the author's work